2019
DOI: 10.3390/ijms20174195
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibroblast Growth Factor 23 in Inflammation and Anemia

Abstract: In patients with chronic kidney disease (CKD), adverse outcomes such as systemic inflammation and anemia are contributing pathologies which increase the risks for cardiovascular mortality. Amongst these complications, abnormalities in mineral metabolism and the metabolic milieu are associated with chronic inflammation and iron dysregulation, and fibroblast growth factor 23 (FGF23) is a risk factor in this context. FGF23 is a bone-derived hormone that is essential for regulating vitamin D and phosphate homeosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 317 publications
(462 reference statements)
0
59
0
Order By: Relevance
“…In the early stages of CKD, serum FGF23 levels can rise 1000-fold above normal values. This condition is determined by the need to maintain acceptable phosphate levels [89]. The overexpression of FGF23 is linked to hypophosphatemic rickets/osteomalacia, in contrast, a decrease in the action of FGF23 results in hyperphosphatemic calcinosis with high 1,25(OH)2D3 levels [90].…”
Section: Fgf23-klotho and Vitamin D Axis In Endocrine-paracrine Renalmentioning
confidence: 99%
“…In the early stages of CKD, serum FGF23 levels can rise 1000-fold above normal values. This condition is determined by the need to maintain acceptable phosphate levels [89]. The overexpression of FGF23 is linked to hypophosphatemic rickets/osteomalacia, in contrast, a decrease in the action of FGF23 results in hyperphosphatemic calcinosis with high 1,25(OH)2D3 levels [90].…”
Section: Fgf23-klotho and Vitamin D Axis In Endocrine-paracrine Renalmentioning
confidence: 99%
“…It seemed that the effect of decreased FGF23 in CharXgen group cannot be fully explained by lowering serum phosphate. In addition, experimental study indicated that inflammation was novel regulator of systemic FGF23 synthesis and secretion [43,44]. Previous report demonstrated IS was able to induce oxidative stress and inflammation [11].…”
Section: Discussionmentioning
confidence: 96%
“…Iron citrate complexes have been shown to capture and reduce phosphate and FGF23 levels in both dialyzed and non-dialyzed CKD patients [53]. As phosphates [56] and FGF23 [57] A significant reduction in the requirement for therapy with erythropoiesis stimulating agents was also reported [60]. Further studies in dialyzed patients are ongoing (ClinicalTrials.gov: NCT04042324).…”
Section: Sucrosomial Ironmentioning
confidence: 99%